Dear readers of and contributors to Biodiversity and Natural History - Leonardo D. Fernández; Carlos Zamora-Manzur (Biodiversity and Natural History, 2015)
Welcome to the first issue of Biodiversity and Natural History, a peer-reviewed, open-access and electronic journal published by the Centro de Estudios en Biodiversidad de Chile (Center for Studies in Biodiversity). The journal was created in 2009 under the name of Boletín de Biodiversidad de Chile with the aim of being a contribution to the dissemination of the Chilean biodiversity and natural history. True to its original purpose, the journal only published Chilean manuscripts in the early years. However, as time went by, the journal also started to receive and publish manuscripts coming from elsewhere in the planet. Accordingly, the journal gradually became an international channel for the scientific promotion and dissemination of biodiversity and natural history and thus, the name of the journal, as well as its original scope and goals were no longer representative.